Genetic variability among Paralaudakia microlepis (Blanford, 1874) (Sauria: Agamidae) populations in the Iranian Plateau - Sanchooli, Nasser; Rastegar-Pouyani, Eskandar; Hosseinian, Saeed (Zootaxa, 2018)
The small scaled rock agama, Paralaudakia microlepis, is an agamid lizard distributed across many parts of the Iranian Plateau. In the present paper, our aim is to study the genetic variability among different populations of this species in Iran. Based on the ND4 mitochondrial gene fragment, we uncovered high levels of genetic variability between three main clades of the species in Iran. Based on these results, the South Khorasan and Fars populations diverged firstly and then the Kerman and the Sistan-Baluchestan populations split. This pattern of divergence suggests an important role of the Zagros Mountain in the differentiation among populations of P. microlepis in Iran during the mid-Miocene. The Zagros uplift and subsequent aridification in the Iranian Plateau might have been involved in the variation among populations of this species because they are restricted to specific ecological niches. The greater genetic distances between the Fars and South Khorasan populations indicated that they have the potential to be described as different subspecies of P. microlepis. Comparison of all P. microlepis, P. erythrogastra and P. caucasia populations using both molecular and morphological characters is needed to make a strong taxonomic decision on the clade as a whole.